Pengaruh Akses Teknologi, Komunikasi dan Informasi (TIK) Terhadap Capaian Pembelajaran Siswa Sekolah Menengah Pertama (SMP) di Indonesia - Meriyanti Meriyanti; Thia Jasmina (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
One of the goals of educational development is that education must be accessible to everyone. Both accessibility and quality of education have to be attained to assure human resource development. Unfortunately, the academic achievement of Indonesian students in recent years is still unsatisfactory. Meanwhile, the development of Information and Communication Technology (ICT) is inseparable from human life. ICT has become one of the solutions to improve educational quality. This study aims to analyze the effect of ICT access on the learning performance of Indonesian junior high school (SMP) students. ICT access in this study focuses on basic facilities and infrastructure that schools must possess based on indicators of sustainable development goals, namely availability of computers, access to the internet, and electricity. This study uses cross-sectional data from regencies/cities in Indonesia in 2018 with the Ordinary Least Square (OLS) model based on the theoretical framework of education production functions using Computer-Based National Examination (UNBK) data as a dependent variable. Study results show that the availability of computers in schools and ICT facilities in households has a significant positive effect on the learning performance of SMP students in Indonesia. Meanwhile, the availability of access to electricity and school internet has not affected the learning performance of SMP students. The independent control variables of school characteristics (the student-to-teacher ratio and class conditions) and socioeconomic characteristics (population density) show significant positive results on the learning performance of SMP students. National examination scores in Eastern Indonesia tend to be lower than those in other regions. In this regard, the government needs to focus on the improvement and equity of ICT resources.